Harmonizing work-life Equilibrium: Unveiling academicians' perspectives in Malaysian Higher Education on work-life balance - Sharmila Devi Ramachandaran; Puspanathan Doraisingam; Riska Nuraini; Sonia Kumari (Social Sciences and Humanities Open, 2025)
The purpose of this study is to investigate work-life balance (WLB) among academicians in Malaysia, with a focus on understanding how they conceptualize WLB within their unique professional and cultural contexts. Despite extensive research on WLB, there is a limited understanding of how academicians, particularly in Malaysia's private higher education sector, perceive and manage the balance between their professional and personal lives. This study addresses this gap by employing a qualitative approach, where academicians are interviewed to explore their conceptualizations of WLB. The significance of this study lies in identifying the key factors that impact WLB among academic staff at Malaysian private universities, offering insights that can guide the creation of tailored WLB programs. The research findings aim to inform policy development and promote a positive WLB culture in academic environments. The originality of this study stems from its focus on the specific challenges faced by academicians in Malaysian private universities, a context that has been largely overlooked in existing WLB literature.